GOOD CORPORATE GOVERNANCE, AUDITOR QUALITY AND AUDITOR OPINION ON EARNING PERSISTENCY - Arfan Ikhsan; Putri Kemala Dewi Lubis; Tiolina Evi; Syahrijal Hidayat; Ratih Kumala (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2023)
Research tries to test good corporate governance (GCG), auditor quality (AQ), and audit opinion (AO) on earning persistence (EP). Earning quality are earning persistent, in this case the earning owned are permanent and not transitory or temporary. Eanring persistence is profit that has the ability to be an indicator of profit for the future period that is generated by the company repeatedly. Research uses GCG, AQ, and AO as independent variables and EP is dependent variable. Research population all publicly traded companies using purposive sampling technique. Research sample is 989 public enterprise registered on Indonesia Stock Exchage (ISX) 2017-2021. This research also test some variables control include absolute accrual value, cash flow volatility (CFV) and sales volatility (SV). The results are: (1) Board commissioner’s independence, institutional ownership, auditor opinion, and auditor quality have a positive effect on earnings persistence. (2) Audit committee meetings don’t affect earnings persistence. (3) For control variables: leverage, cash flow volatility (CFV), and sales volatility (SV) don’t affect earnings persistence (EP).